The relationship between neutrophil to lymphocyte ratio and myocardial bridge - Aksu, Ekrem; Avci, Deniz; Cikim, Gurkan (International Journal of Research in Medical Sciences, 2016)
Background: Although myocardial bridge (MB) is a benign congenital anomaly, clinical trials have shown it to cause increased risk of atherosclerosis, which is a low-grade chronic inflammatory disease. The neutrophil-lymphocyte ratio (NLR) is an inflammatory indicator for mortality and morbidity in atherosclerotic heart disease. In this study, NLR was investigated in patients with MB. Methods: A retrospective evaluation was made of patients admitted to our clinic for coronary angiography from 01st January 2014 to 31st December 2015. Patients included in the study were those diagnosed with MB and no evidence of atherosclerosis after coronary angiography and patients diagnosed with normal coronary vascularity. The NLR was calculated from the biochemical and hematological parameters based on the results of pre-angiographic values. Results: Evaluation was made of 53 patients with MB (mean age: 56.70±11.45 years, 73.6% male), and 59 patients with normal coronary vascularity (mean age: 52.25±12.42 years, 39% male). No significant difference was determined between the groups in respect of biochemical or hematological parameters or in NLR values (2.34±0.88 versus 2.56±1.66; p=0.384). Conclusions: The results of this study showed no relationship between MB and the inflammatory indicator of NLR.